Trigonometry
posted by Greg .
What value(s) of theta solve the following equation? cos^2(theta)cos(theta)6=0?
I try plugging in different numbers but I am not sure exactly what I am looking for in order to solve?

cos^2 Ø  cosØ  6 = 0
let cosØ = x , then we get
x^2  x  6 = 0
(x3)(x+2) = 0
x = 3 or x = 2
then cosØ = 3 or cosØ = 2
both of these are not possible, since the cosine is defined only between 1 and +1
there is no solution to your equation 
also, you coul dhave reasoned thus:
cos^2θ <= 1
1 <= cosθ <= 1
no way could you have cos^2θ  cosθ = 6
Respond to this Question
Similar Questions

science
Sitting on a horizontal track is a mass of 10kg. One end of the track is raised untill the mass just begins to slip. If the coeffieient of static friction is .4 what is the minimum angle at which the mass begins to slip? 
Calculus
I wanted to confirm that I solved these problems correctly (we had to convert the polar curves to Cartesian equations). 1.rcos(theta)=1 x=1 2.r=2*sin(theta)+2*cos(theta) r^2=2rsin(theta)+2rcos(theta) x^2+y^2=2y+2x (a little unsure … 
Trigonometry
Okay, I have been given a trigonometric equation to solve (sin^2(theta) + cos(theta) = 2). So far, I have been able to use the Pythagorean identity to get (cos^2(theta) + cos(theta)  1 = 0), which I then multiplied by 1 on both … 
Precalculus 2
Similiarly to a question I asked previously I took the same approach. the problem is: what value(s) of theta solve the following equation? 
Trigonometry
Thank you STEVE!!!!! Suppose that Cos (theta) = 1/square root 2 if 0<equal to theta , pi/2 then sin(theta) = tan (theta) = If 3pi/2 less than equal to theta , 2pi then sin(theta) = tan (theta) = I know the trig functions but I feel … 
Math  Trigonometry
Let f(x) be a polynomial such that f(cos theta) = cos(4 theta) for all \theta. Find f(x). (This is essentially the same as finding cos(4 theta) in terms of cos theta; we structure the problem this way so that you can answer as a polynomial. … 
Mathamatics
Solve the following trigonometry identities. a) 1cos2(theta) = sin(theta)cos(theta)/cot(theta) b) (1cos2(theta))(1tan2(theta))=sin2(theta)2sin4(theta)/1sin2(theta) *its supposed to be cos to the power of two, sin to the power … 
Trigonometry
Use a sum of difference identity to write the expression as a single function theta: cos(theta  pi). Okay so I know we will use cosAcosA+sinBsinB I got: cos(theta)cos(theta)sin(pi)sin(pi) I don't know how to solve from here and I'm … 
Trigonometry
Prove the following identities: 1. (tan theta  sin theta)^2 + (1cos theta)^2 = (1sec theta) ^2 2. (12cos^2 theta) / sin theta cos theta = tan theta  cot theta 3. (sin theta + cos theta ) ^2 + (sin theta  cos theta ) ^2 = 2 Thank … 
Trigonometry
Prove the following identities: 1. (tan theta  sin theta)^2 + (1cos theta)^2 = (1sec theta) ^2 2. (12cos^2 theta) / sin theta cos theta = tan theta  cot theta 3. (sin theta + cos theta ) ^2 + (sin theta  cos theta ) ^2 = 2 Thank …